Nutrition handbook for food processors - Henry, C.J.K. (Woodhead Publishing, 2011)
This book brings together an international team of experts to summarise key findings on diet and nutrient intake, the impact of nutrients on health, and how food processing operations affect the nutritional quality of foods.